Modelo metodológico y didáctico para el desarrollo del razonamiento matemático - Zenteno Ruiz, Flaviano Armando (2017)
The conclusive research is that the effects produced by the methodological and didactic model in the development of mathematical reasoning; the general research problem was: How does the methodological and didactic model influence the development of mathematical reasoning in the students of the Laboratory of Pedagogical Research and Innovation of the National University Daniel Alcides Carrión of Pasco -2016? whose theoretical supports were: Pólya (1975), Corvalán (1995), Perelman (1978), and Zenteno (2005), on teaching mathematics learning and teaching skills and strategies; the research methodology considered the pre-experimental pretest and post-test design, with established groups, the research instruments were validated through expert judgment, the results allow giving conclusions such as: the proposal is viable because the experimental group shows an average of 61.03; coefficient of variation 0.28 and the statistic Z=8.56 which validates the research hypothesis established to show that it significantly influences the development of mathematical reasoning, highlighting the constant practice of autonomy, self-direction and self-regulation, since the UNDAC Laboratory of Pasco is an educational institution of Regular Basic Education.